EVALUASI POLA RUANG BERBASIS KERAWANAN BANJIR DI KABUPATEN PIDIE - Achmad Yamani; Ernan Rustiadi; Widiatmaka Widiatmaka (Diponegoro University, 2015)
Pidie is one of the districts in Aceh Province that has been suffering from flooding. Frequent disasters, especially flooding associated with various causative factors, need mitigation efforts. An appropriate land use planning by considering the risk aspects especially in flood is an important step. Objectives of this study are to determine the factors influencing the flood hazard, to map the areal distribution vulnerable to flood, to analyze the relations of land use in the flood hazard area, and to analyze the relations between the planned spatial pattern and the flood hazard area. ,Multicriteria analysis was used to determine the factors influencing the flood hazard. Spatial analysis was used in mapping the class of flood hazard, the relations of land use in the flood hazard area, and the relations between the planned spatial pattern and the flood hazard area. The results show that the main factors influencing flood vulnerability are land use/cover (0.408), rainfall (0.266), and slope (0.184). Based on the classification of flood vulnerability, the area can be divided into more vulnerable (37.75 %), less vulnerable (30 %), and mildly vulnerable (22.76 %). The vulnerability classes of the land use/cover are: less vulnerable (99.99 %) and more vulnerable (97.57 %) dominated by forest cover; mildly vulnerable (51.07%) and vulnerable (92.65%) dominated by mixed farming; and very vulnerable (97%) dominated by settlement. The flood vulnerability of the planned spatial pattern can be classified as follows: 95.44 % of the conservation area is dominated by less vulnerable and more vulnerable, while 71.20 % of the cultivation area can be categorized into mildly vulnerable, vulnerable and very vulnerable.